Saxenda, Ozempic, and Mounjaro: a Comparative Analysis of The Weight Loss Medications and Their Side Effects in Najaf, Iraq - Mohammed, Zainab Sajid; Al-Kraity, Wijdan Rajh Hamza (Medical Science Journal for Advance Research, 2026)
Background: Pharmacological management of obesity has occurred through weight loss injection, such as Saxenda, Ozempic, and Mounjaro. These agents control appetite, satiety and glucose metabolism that stimulate caloric intake and weight loss. Although they are generally safe, any drug has the possibility of causing side effects primarily the gastrointestinal ones and infrequent severe effects, such as pancreatitis. Purpose: This research was intended to determine the effectiveness of Saxenda, Ozempic and Mounjaro and their side effects in relation to the reduction of body weight in adults in Najaf, Iraq. Methodology: The study involved a cross-sectional study in the period between January and April 2025 in Najaf. Fifty adult patients who visited nutrition and obesity clinics were involved. The demographic, body weight, and side effect data collected was through self-administered questionnaires. The use of descriptive statistics, paired t-tests, ANOVA and regression analyses were used. Findings: The majority of them were women aged 20-45 years. The most common used (52%), Ozempic (30%), and Mounjaro (18%). There was a significant weight reduction (p < 0.01) with Mounjaro recording the highest mean reduction. The prevalence of gastrointestinal side effects was highest, but with a minor variation in drugs. The regression analysis showed that physical activity and type of medication played a major role in weight loss outcomes. Conclusion: Saxenda, Ozempic, and Mounjaro are viable in reducing weight in the short term. Mounjaro caused the weight loss to the maximum. The side-effects were generally mild. It is advisable to incorporate these medications with lifestyle changes in order to handle obesity in the best way possible.